Associations of eHealth literacy with health‐promoting behaviours among hospital nurses: A descriptive cross‐sectional study. (20th April 2018) - Cho, Hyeonmi; Han, Kihye; Park, Bu Kyung
Abstract: Aims: To investigate the associations of eHealth Literacy with health‐promoting behaviours among hospital nurses in South Korea. Background: Health‐promoting behaviours of nurses are crucial for their own improved health and health‐related behaviours of patients. eHealth literacy refers to the ability to search, understand and evaluate health information available online. With the growing use of the Internet, eHealth literacy is emerging as an important factor enhancing health‐promoting behaviours. Design: Descriptive cross‐sectional design with self‐reported questionnaires. Methods: Data were collected between March–May 2016 from five hospitals in South Korea. Health‐promoting behaviours and eHealth literacy were assessed using Health Promoting Lifestyle Profile‐II and K‐eHEALS, respectively. Multiple linear regression models were used to examine the associations of eHealth literacy and health‐promoting behaviours. Results: Nurses with high level of eHealth literacy had significantly positive overall health‐promoting behaviours, stress management, interpersonal relations, self‐actualization and health responsibility, but not for nutrition and physical activity. Conclusion: Improving eHealth literacy through various strategies could be an effective way to boost health‐promoting behaviours among nurses. However, improvement of actual health‐promoting behaviours such as nutrition and physical activity will require systematic and organizational changes.